Method for preparing novel ultra-high performance concrete material from plant ash

By using processed plant ash and natural plant fibers in ultra-high performance concrete, the problems of low reactivity and high energy consumption emissions of traditional admixtures are solved, significantly improving the mechanical properties and durability of concrete while achieving environmental benefits. .

CN119330661APending Publication Date: 2025-01-21FUJIAN HUIFENG CONSTR TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411427865.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete has problems of high energy consumption and large carbon dioxide emissions during the production process, and the traditional blends have low reactivity, making it difficult to significantly improve the strength and durability of concrete.

Method used

By introducing treated plant ash and natural plant fibers, dry mixing and wet mixing processes are used to form a uniform ultra-high performance concrete slurry. Plant ashes are screened, crushed, alkali treated and heat treated to activate their active silica; natural plant fibers are alkali treated and hot pressed to improve their compatibility with the cement matrix.

Benefits of technology

It significantly improves the compressive strength, flexural strength and durability of concrete, reduces cement consumption, reduces carbon emissions, achieves environmental benefits, and improves the material's compactness and permeability resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330661A_ABST
    Figure CN119330661A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, and discloses a method for preparing an ultra-high performance concrete new material by using plant ash, the method comprises the following steps: carrying out alkali treatment and heat treatment on the plant ash to enhance the volcanic ash activity of the plant ash, and uniformly distributing bamboo fibers as a reinforced phase material after chemical and physical treatment in concrete; through reasonable proportion design, the compressive strength and the breaking strength of the concrete are improved, the porosity is remarkably reduced, the impermeability and the freeze-thaw resistance are enhanced, and good fluidity is kept; and the plant ash partially replaces cement, so that the cement consumption is reduced, the carbon emission is reduced, and good environmental protection benefits and sustainable development values are achieved. The method is suitable for manufacturing high-strength and high-durability building materials, and is particularly suitable for engineering application of bridges, super high-rise buildings, infrastructures and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing a new ultra-high performance concrete material by utilizing plant ash. Background Art

[0002] Ultra-high performance concrete (UHPC), as a new type of building material, has been widely used in high-strength and high-durability building structures due to its excellent mechanical properties, crack resistance and durability. However, the existing ultra-high performance concrete mainly relies on the use of a large amount of high-quality cement, silica fume and other mineral admixtures, resulting in high energy consumption and large amounts of carbon dioxide emissions during its production process, which is not conducive to the promotion of green buildings. In addition, the crack resistance of traditional UHPC is mainly achieved by introducing steel fibers or synthetic fibers, but these materials are expensive and involve the consumption of a large amount of non-renewable resources during the production process, increasing the environmental burden.

[0003] In the existing technology, although fly ash, slag and other industrial by-products are added as substitute materials to reduce cement usage and improve concrete performance, these materials have low reactivity and cannot fully react with the cement matrix, making it difficult to significantly improve the strength and durability of concrete. At the same time, although steel fibers or synthetic fibers can enhance the crack resistance of UHPC, they are relatively rigid and unevenly distributed in the concrete matrix, which easily forms crack concentration points, resulting in unsatisfactory crack resistance. Synthetic fibers are prone to aging in high temperature environments and have poor long-term durability.

[0004] Therefore, how to find a material alternative that can improve mechanical properties, crack resistance, and environmental benefits while maintaining or improving the performance of UHPC has become a major challenge in the current technology field. The shortcomings of these existing technologies limit the wider application of UHPC in modern construction, especially in construction projects that focus on environmental protection and sustainable development, which urgently need technological innovation and improvement. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a new ultra-high performance concrete material using plant ash. By introducing treated plant ash and natural plant fibers, while maintaining or improving the mechanical properties of concrete, its crack resistance and durability are significantly improved, and the amount of cement used is reduced to achieve environmental benefits.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a new ultra-high performance concrete material using plant ash, comprising the following steps:

[0007] The plant ashes are screened, crushed, chemically treated and thermally treated to obtain plant ashes with a particle size of 5-15 microns;

[0008] Ordinary Portland cement, silica fume, fine aggregate, ultrafine powder and treated plant ash are dry-mixed and stirred;

[0009] Gradually add water and superplasticizer mixed solution to the dry mix, and gradually add plant ash while stirring;

[0010] Natural plant fibers are added to the wet mix and mixed at medium speed followed by high-speed mixing to obtain a uniform ultra-high performance concrete paste.

[0011] Preferably, the processing of plant ash includes:

[0012] Sieving: Use a 200-mesh screen to sieve the plant ashes to remove particles larger than 75 microns;

[0013] Crushing: The sieved plant ashes are crushed by crushing equipment to control the average particle size of the ashes to 5-15 microns.

[0014] Preferably, the chemical treatment of plant ash comprises the following steps:

[0015] Using 2-5% sodium hydroxide solution to perform alkali treatment on plant ashes, the treatment temperature is controlled at 60-70°C, and the treatment time is 2-4 hours;

[0016] The treated plant ashes were washed with distilled water until the pH of the solution was close to neutral;

[0017] The cleaned plant ashes are dried in a constant temperature drying oven at 50-60°C for 12-24 hours.

[0018] Preferably, the heat treatment temperature of the plant ash is 600-700° C., and the insulation time is 1-2 hours.

[0019] Preferably, the silicon dioxide content of the treated plant ash is 60-75%.

[0020] Preferably, the processing of the natural plant fiber comprises the following steps:

[0021] The fiber is alkali treated with a 3-5% sodium hydroxide solution at a temperature of 60-70°C for 2-3 hours;

[0022] The alkali treated fiber is subjected to heat pressing treatment at a temperature of 80-100°C, a pressure of 10-15 MPa, and a time of 30-60 minutes.

[0023] Preferably, the ratio of cement, plant ash, silica fume, fine aggregate and ultrafine powder is:

[0024] Cement: silica fume: plant ash: limestone powder: quartz sand: water = 1: (0.15-0.25): (0.2-0.3): (0.05-0.1): (1-1.2): (0.18-0.22).

[0025] Preferably, the natural plant fiber is bamboo fiber, the fiber content is 2-3% of the total volume of the wet mix, and the fiber length is 8-15 mm.

[0026] Preferably, the superplasticizer is a polycarboxylic acid-based water reducer, the dosage of which is 0.8-1.2% of the mass of the cementitious material, and the superplasticizer is added gradually in 3-4 times for wet mixing.

[0027] The present invention also provides the use of the ultra-high performance concrete prepared by the method in highway bridges, building structures and infrastructure.

[0028] The present invention provides a method for preparing a new ultra-high performance concrete material using plant ash. It has the following beneficial effects:

[0029] 1. The present invention significantly improves the compressive strength and flexural strength of concrete by using treated plant ash as an admixture. The active silicon dioxide (SiO2) in the plant ash after alkali treatment and heat treatment can react with calcium hydroxide (Ca(OH)2) in the cement matrix to generate a large amount of calcium silicate hydrate (CSH) gel, which fills the pores in the concrete and improves the compactness and strength of the concrete.

[0030] 2. By using natural plant fiber (bamboo fiber) as a reinforcing material, the present invention significantly enhances the crack resistance and toughness of concrete. Bamboo fiber has good dispersibility and toughness, and can form a three-dimensional network in the concrete matrix, effectively bridging cracks and delaying the expansion of cracks. Compared with traditional steel fibers, bamboo fibers show better effects in crack control, reducing the width and number of cracks, thereby improving the crack resistance and toughness of concrete, and are particularly suitable for building materials with high requirements for impact resistance and crack resistance.

[0031] 3. The present invention reduces dependence on traditional mineral resources and significantly reduces the carbon footprint of concrete by partially using plant ash to replace cement or silica fume. A large amount of carbon dioxide is produced during the production of cement, and the use of plant ash can reduce the amount of cement, thereby achieving the purpose of reducing carbon emissions. At the same time, plant ash, as a by-product of biomass combustion, is a renewable resource with good environmental benefits. By rationally utilizing plant ash, effective recycling and sustainable utilization of resources can be achieved, which is in line with the development trend of green building materials.

[0032] 4. In the present invention, the treated plant ash effectively improves the microstructure compactness of concrete. The high reactivity of active SiO2 in the ash can accelerate the formation of CSH gel, fill the pores inside the concrete, greatly reduce its porosity, and thus improve the compactness of the overall material. The dense microstructure not only improves the mechanical properties, but also significantly enhances the material's anti-permeability and anti-carbonation properties, ensuring that the concrete maintains stable performance during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Please see attached Figure 1 The present invention provides a method for preparing a new ultra-high performance concrete material using plant ash. By using plant ash as the main admixture and combining it with treated natural fibers, the present invention has significant innovations in improving the mechanical properties, durability and environmental protection of ultra-high performance concrete. This method reduces the carbon emissions of concrete by effectively replacing traditional admixtures (such as silica fume) and cement, and significantly improves the mechanical properties and crack resistance of concrete. The following is a description of the steps of the method of the present invention.

[0036] 1. Selection and processing of raw materials

[0037] Sources and treatment of plant ash

[0038] The choice of plant ash comes from wood or other biomass with a high silica (SiO2) content. The burned plant ash not only has pozzolanic activity, but also undergoes a series of processing steps to remove impurities and improve its reactivity with the cement matrix.

[0039] The processing of plant ash includes:

[0040] 1. Screening: Use a 200-mesh screen to screen the plant ashes to remove particles larger than 75 microns. The purpose of screening is to remove impurities such as unburned organic matter and larger particles, thereby improving the purity of the ashes.

[0041] 2. Crushing: The sieved ash is crushed in a ball mill for 30-45 minutes to obtain particles with a particle size of 5-15 microns. Controlling the particle size to micron level not only increases the specific surface area of ​​the ash, but also improves its pozzolanic reactivity, which helps the bonding between the ash and the cement matrix.

[0042] 3. Alkali treatment: In order to remove the incompletely burned organic matter and other impurities in the ash, the ash is treated with 2-5% sodium hydroxide solution at a temperature of 60-70°C for 2-4 hours. Alkali treatment can effectively remove the residual organic matter in the ash and enhance the chemical stability and volcanic ash activity of the ash.

[0043] 4. Cleaning and drying: The ash after alkali treatment is repeatedly cleaned with distilled water until the pH value is close to neutral to remove residual alkaline substances. Then it is dried in a constant temperature drying oven at 50-60℃ for 12-24 hours to ensure that the moisture content of the ash is moderate to ensure its dispersibility in the subsequent mixing process.

[0044] 5. Heat treatment: In order to further improve the pozzolanic reactivity of plant ash, the treated ash is heated to 600-700℃ for 1-2 hours. This high temperature treatment process can completely remove the residual organic matter in the ash, while activating the SiO2 component, improving its reactivity and enabling it to better undergo secondary hydration reaction with the cement matrix.

[0045] Through these treatment steps, the active silica in the plant ash can react with the calcium hydroxide (Ca(OH)2) in the cement matrix to form calcium silicate hydrate (CSH) gel. This secondary reaction generates CSH gel that can fill the pores in the concrete and increase its density, thereby significantly improving the compressive strength and durability of the concrete.

[0046] Processing of natural plant fibers

[0047] The present invention selects natural plant fiber, especially bamboo fiber, as reinforcing phase material. Bamboo fiber has high strength and toughness, and after chemical and physical modification, its compatibility with cement matrix and crack resistance can be further improved.

[0048] The processing of bamboo fiber includes:

[0049] 1. Alkali treatment: Use 3-5% sodium hydroxide solution to treat bamboo fiber with alkali, the treatment temperature is 60-70℃, and the treatment time is 2-3 hours. The purpose of alkali treatment is to remove lignin and hemicellulose on the fiber surface, increase the roughness of the fiber surface, and enhance its bonding with the cement matrix.

[0050] 2. Cleaning and drying: The treated bamboo fiber is repeatedly cleaned with distilled water until the pH value of the solution is close to neutral, and then dried in a drying oven at 50-60℃ for 12-24 hours to ensure that the fiber is completely dry.

[0051] 3. Hot pressing and stretching treatment: The dried bamboo fiber is further subjected to hot pressing treatment at a temperature of 80-100°C, a pressure of 10-15 MPa, and a time of 30-60 minutes. In addition, the bamboo fiber is stretched by 2-5% through a stretching device to improve the dispersion and mechanical strength of the fiber.

[0052] After being processed, natural plant fibers play a role similar to steel fibers in concrete, bridging cracks when concrete is under tension, thereby delaying the expansion of cracks. The uniform distribution of fibers not only improves the tensile strength of concrete, but also significantly enhances its crack resistance, extending the service life of concrete in complex stress environments.

[0053] 2. Concrete mix design and mixing

[0054] Material ratio

[0055] In order to achieve the best performance of ultra-high performance concrete, the present invention provides a precise mix design that takes into account the fluidity, compressive strength, crack resistance and durability of the concrete.

[0056] Cement: silica fume: plant ash: limestone powder: quartz sand: water = 1: 0.15-0.25: 0.2-0.3: 0.05-0.1: 1.0-1.2: 0.18-0.22;

[0057] Superplasticizer: Use polycarboxylic acid water reducer with the dosage of 0.8-1.2% of the total mass of cementitious materials to ensure that the concrete has good fluidity under low water-cement ratio conditions.

[0058] In this mix design, plant ash replaces part of silica fume and cement, significantly reducing cement usage and thus reducing carbon dioxide emissions. At the same time, the addition of limestone powder further improves the material's density and long-term durability.

[0059] Mixing process

[0060] The mixing process of concrete is a key step to ensure the performance of the material. The mixing process should ensure the uniform distribution of each component and maximize the uniformity and density of the material.

[0061] The mixing process includes the following steps:

[0062] 1. Dry mixing process

[0063] Add cement, quartz sand, limestone powder, silica fume and treated plant ash into the mixer according to the proportion, and stir at low speed for 2-4 minutes to ensure that the dry materials are fully mixed.

[0064] 2. Wet mixing process

[0065] Mix water and superplasticizer in advance, and gradually add them to the dry mix in 3-4 times. Stir for 3-5 minutes after each addition of water to ensure that the water and dry materials are fully combined.

[0066] During the wet mixing process, gradually add the treated plant ash and continue stirring for 4-6 minutes to ensure uniform mixing of the ash and cement matrix.

[0067] 3. Fiber addition and high-speed stirring

[0068] Add the treated bamboo fiber into the blender gradually in 3 batches and stir for 5-7 minutes after each addition to prevent the fibers from agglomerating.

[0069] After all materials are added, the mixer is switched to high-speed stirring mode and stirred for 3-5 minutes to ensure homogenization of the slurry and uniform distribution of the fibers.

[0070] Through the steps of wet mixing and high-speed stirring, the ash and fibers can be evenly dispersed in the concrete matrix. The SiO2 in the plant ash reacts with the calcium hydroxide in the cement matrix to form CSH gel, which fills the pores and improves the density of the concrete. At the same time, the natural plant fibers form a three-dimensional dispersed network in the concrete matrix, enhancing the crack resistance and toughness of the concrete.

[0071] The ultra-high performance concrete prepared by the present invention is widely used in various engineering structures requiring high strength and high durability, including highway bridges, super high-rise buildings, large infrastructure, etc. The main properties of the material are as follows:

[0072] Compressive strength: The compressive strength of concrete can reach over 120MPa, meeting the application requirements of ultra-high performance concrete in high-load-bearing structures.

[0073] Flexural strength: The treated bamboo fiber enhances the flexural properties of concrete, and the flexural strength can reach over 20MPa.

[0074] Durability: The material has excellent anti-freeze-thaw, anti-penetration and anti-carbonation properties, and can be used for a long time in harsh environments, significantly extending the service life of buildings and infrastructure.

[0075] The high compressive strength of the UHPC prepared by the present invention comes from the active reaction of plant ash and the dense microstructure; while the crack resistance and durability are due to the uniform distribution of fibers and their tensile properties. The synergistic effect of ash and fiber makes the concrete of the present invention show excellent comprehensive performance in both mechanical properties and environmental protection characteristics.

[0076] In general, the present invention provides a new method for preparing ultra-high performance concrete based on plant ash and natural fiber, which significantly improves the compressive strength, crack resistance and durability of concrete through reasonable mix design and mixing process. The method achieves the goal of low carbon and environmental protection by replacing part of cement and traditional admixtures, and provides strong support for the development of green building materials. At the same time, the technical solution of the present invention is simple and easy to implement, and has broad application prospects and economic benefits.

[0077] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.

[0078] Example 1: Standard UHPC preparation based on plant ash and bamboo fiber

[0079] raw materials

[0080] Ordinary Portland cement: 100 parts

[0081] Plant ash: 20 parts (replaces part of silica ash)

[0082] Silica fume: 20 parts

[0083] Limestone powder: 7.5 parts

[0084] Quartz sand: 110 parts

[0085] Water: 18.5 parts

[0086] Polycarboxylic acid water reducing agent: 1.0 part (based on the total mass of cementitious materials)

[0087] Bamboo fiber: volume ratio is 2.5%, fiber length is 12mm

[0088] Processing conditions

[0089] Plant ash treatment: sieved through a 200-mesh sieve and ball-milled to 5-15 microns; alkali treatment concentration is 3% NaOH solution, treatment temperature is 60°C, time is 3 hours, followed by heat treatment, temperature is controlled at 650°C, insulation time is 1.5 hours.

[0090] Bamboo fiber treatment: The fiber was treated with 4% NaOH solution at a temperature of 65°C for 2.5 hours; after the fiber was dried, it was hot-pressed at a temperature of 90°C, a pressure of 12 MPa, and a time of 45 minutes.

[0091] Mixing process

[0092] Dry mixing time: 2.5 minutes;

[0093] Wet mixing time: Stir for 4 minutes after each addition of water, adding ash gradually;

[0094] Fiber addition time: 5 minutes stirring per batch, 3 minutes at high speed.

[0095] This UHPC is used for prefabricated beam components of highway bridges. It has good compressive strength and durability. The compressive strength reaches 130MPa and the flexural strength is 25MPa, with extremely high durability.

[0096] Example 2: Preparation of UHPC with high crack resistance

[0097] raw materials

[0098] Ordinary Portland cement: 100 parts

[0099] Plant Ashes: 30

[0100] Silica fume: 15 parts

[0101] Limestone powder: 10 parts

[0102] Quartz sand: 100 parts

[0103] Water: 18 parts

[0104] Polycarboxylic acid water reducer: 1.1 parts

[0105] Natural fiber (bamboo fiber): 3.0% volume ratio, fiber length 10mm

[0106] Processing conditions

[0107] Plant ash treatment: Alkali treatment concentration is 4% NaOH solution, treatment temperature is 70°C, time is 2 hours, heat treatment temperature is 680°C, and insulation is 1 hour.

[0108] Bamboo fiber treatment: 5% NaOH solution was used for treatment. After the fiber was dried, it was hot pressed at 90°C, with a pressure of 15 MPa for 60 minutes.

[0109] Mixing process

[0110] Dry mixing time: 3 minutes;

[0111] Wet mixing time: Stir for 5 minutes each time after adding water, gradually adding plant ash to ensure even mixing;

[0112] Fiber addition time: Add in 3 batches, stirring for 7 minutes each time.

[0113] Used for large concrete slab structures that are sensitive to cracks and require high crack resistance. The compressive strength reaches 125MPa and the flexural strength is 30MPa, which significantly improves the crack control ability and extends the life of concrete.

[0114] Example 3: Rapid prototyping of UHPC

[0115] raw materials

[0116] Ordinary Portland cement: 100 parts

[0117] Plant Ashes: 25

[0118] Silica fume: 18 parts

[0119] Limestone powder: 8 parts

[0120] Quartz sand: 105 parts

[0121] Water: 19 parts

[0122] Polycarboxylic acid water reducer: 0.9 parts

[0123] Bamboo fiber: volume ratio 2%, fiber length 8mm

[0124] Processing conditions

[0125] Plant ash treatment: Alkali treatment concentration is 2.5% NaOH solution, treatment temperature is 60°C, time is 3 hours, followed by heat treatment, temperature is 620°C, and insulation is 1 hour.

[0126] Bamboo fiber treatment: treated with 3% NaOH solution, and no hot pressing after drying.

[0127] Mixing process

[0128] Dry mixing time: 2 minutes;

[0129] Wet mixing time: Stir for 3 minutes after adding water gradually;

[0130] Fiber addition time: Add in 2 batches, stir for 6 minutes each time, and stir at high speed for 2 minutes.

[0131] Used for rapid prototyping of precast concrete components, the concrete has a faster early strength development. The compressive strength reaches 80MPa within 24 hours and 125MPa in 28 days, which is suitable for emergency repair or rapid construction scenarios.

[0132] Example 4: Preparation of UHPC with ultra-high toughness

[0133] raw materials

[0134] Ordinary Portland cement: 100 parts

[0135] Plant Ashes: 35

[0136] Silica fume: 20 parts

[0137] Limestone powder: 5 parts

[0138] Quartz sand: 115 parts

[0139] Water: 20 parts

[0140] Polycarboxylic acid water reducer: 1.2 parts

[0141] Bamboo fiber: volume ratio is 2.8%, fiber length is 14mm

[0142] Processing conditions

[0143] Plant ash treatment: Alkali treatment concentration is 3.5% NaOH solution, treatment temperature is 70°C, time is 2 hours, followed by heat treatment, temperature is 650°C, and heat preservation is carried out for 1.5 hours.

[0144] Bamboo fiber treatment: 4.5% NaOH solution was used for treatment. After the fiber was dried, it was hot-pressed at 80°C, with a pressure of 10 MPa for 45 minutes.

[0145] Mixing process

[0146] Dry mixing time: 2.5 minutes;

[0147] Wet mixing time: Stir for 4 minutes each time water is added;

[0148] Fiber addition time: Add in 3 batches, stir for 5 minutes each time, and stir at high speed for 3 minutes.

[0149] This UHPC is used for impact-resistant structures and high-dynamic-load bridges, which require extremely high toughness. The compressive strength is 135MPa, the flexural strength reaches 28MPa, and it exhibits excellent crack toughness.

[0150] Example 5: UHPC preparation for extreme climate conditions

[0151] raw materials

[0152] Ordinary Portland cement: 100 parts

[0153] Plant ashes: 22 parts

[0154] Silica fume: 17 parts

[0155] Limestone powder: 9 parts

[0156] Quartz sand: 120 parts

[0157] Water: 18 parts

[0158] Polycarboxylic acid water reducer: 1.1 parts

[0159] Bamboo fiber: volume ratio is 3%, fiber length is 15mm

[0160] Processing conditions

[0161] Plant ash treatment: Alkali treatment concentration is 4% NaOH solution, treatment temperature is 70°C, time is 3 hours, followed by heat treatment, temperature is 680°C, and heat preservation is carried out for 2 hours.

[0162] Bamboo fiber treatment: 5% NaOH solution was used for treatment. After the fiber was dried, it was hot-pressed at 100°C, with a pressure of 12 MPa for 60 minutes.

[0163] Mixing process

[0164] Dry mixing time: 3 minutes;

[0165] Wet mixing time: stir for 5 minutes after adding water;

[0166] Fiber addition time: Add in 3 batches, stir for 6 minutes each time, and stir at high speed for 4 minutes.

[0167] This UHPC is designed for infrastructure construction in extreme climate conditions, such as bridges and roads in cold regions. It exhibits extremely strong freeze-thaw resistance and durability, with a compressive strength of 140MPa and a flexural strength of 22MPa, and maintains excellent mechanical properties after 300 freeze-thaw cycles.

[0168] In order to better highlight the technical advantages of the present invention, the above method is described in detail below through comparative experiments combined with specific embodiments.

[0169] Comparative experiment 1: Comparative experiment between plant ash and traditional admixtures (silica fume, fly ash)

[0170] Experimental group: the plant ash formula of the present invention: the plant ash after alkali treatment and heat treatment was used to partially replace the silica ash.

[0171] Comparative Example 1: Traditional silica ash formula: silica ash is used entirely without plant ash.

[0172] Comparative Example 2: Traditional fly ash formula: fly ash is used as an admixture to replace part of the silica ash, and no plant ash is used.

[0173] The three sets of concrete formulas are as follows:

[0174]

[0175] Experimental steps:

[0176] 1. Plant ash treatment (applicable only to the present invention):

[0177] Sieving: Sieve the plant ashes using a 200 mesh screen to remove particles larger than 75 microns.

[0178] Grinding: Grind to 5-15 microns by ball mill.

[0179] Alkali treatment: Use 3% NaOH solution at 60°C for 3 hours, then wash to neutrality and dry at 50-60°C for 12 hours.

[0180] Heat treatment: Heat treatment at 650℃ for 1.5 hours to activate the active SiO2 in the ash.

[0181] 2. Bamboo fiber treatment (same for all groups):

[0182] The surface of the substrate was treated with 4% NaOH solution at 65°C for 2.5 hours, and then dried and hot-pressed (90°C, 12 MPa, 45 minutes).

[0183] 3. Dry mixing:

[0184] Add cement, quartz sand, limestone powder, silica fume (or plant ash, fly ash) into the mixer according to the formula and stir at low speed for 2.5 minutes.

[0185] 4. Wet mixing:

[0186] The mixed solution of water and polycarboxylic acid water reducer is gradually added in 3 times, and wet mixing is stirred for 4 minutes each time. Plant ash (or silica ash, fly ash) is gradually added.

[0187] 5. Fiber addition and high-speed stirring:

[0188] Add the bamboo fiber in 3 batches, stirring for 5 minutes each time, and stirring at high speed for 3 minutes.

[0189] 6. Molding and maintenance:

[0190] The slurry was poured into a mold and subjected to vibration compaction treatment. After molding, it was cured under standard conditions (20° C., 95% humidity) for 28 days.

[0191] The experimental results are shown in the following table:

[0192]

[0193] From the data in the above table, we can get:

[0194] 1. Comparison of mechanical properties:

[0195] The UHPC using plant ash in the present invention has a 28-day compressive strength of 135 MPa, which is significantly higher than that of Comparative Example 1 (120 MPa) and Comparative Example 2 (110 MPa). In terms of flexural strength, the plant ash group reaches 28 MPa, which is also better than the silica ash group and the fly ash group.

[0196] This improvement is mainly because the active SiO2 in the plant ash is activated after alkali treatment and heat treatment, and can fully react with the calcium hydroxide (Ca(OH)2) in the cement matrix to generate more CSH gel, which further fills the pores in the concrete and enhances its strength.

[0197] 2. Comparison between fluidity and slump:

[0198] The slump of the three groups was not much different, indicating that the plant ash had limited effect on the fluidity of concrete and maintained good construction performance.

[0199] 3. Porosity and impermeability analysis:

[0200] The porosity of the plant ash group of the present invention is relatively low, only 4.5%, which indicates that its microstructure is more compact. The low porosity brings better impermeability, and the water penetration depth is 12 mm, which is better than the silica ash group (15 mm) and the fly ash group (18 mm).

[0201] The CSH gel produced by plant ash has a higher content (38%), which effectively reduces the pores and forms a denser microstructure, thereby improving the anti-seepage performance.

[0202] 4. Durability test (freeze-thaw cycle loss rate):

[0203] After 100 freeze-thaw cycles, the mass loss rate of the plant ash group was 2.1%, which was significantly lower than that of the silica fume group (3.5%) and the fly ash group (4.0%). This shows that plant ash can significantly improve the durability of concrete, especially its long-term performance in extreme climates.

[0204] After alkali treatment and heat treatment, the active SiO2 in plant ash is effectively activated and can react with cement hydration product Ca(OH)2 to form CSH gel. This reaction not only fills the pores in the concrete, but also improves the density and compressive strength of the matrix. Compared with traditional silica fume and fly ash, plant ash provides stronger pozzolanic reaction ability, and because of its large specific surface area, it can fully contact and react with calcium hydroxide in the cement matrix, further improving the mechanical properties.

[0205] In addition, the dense microstructure brought by plant ash not only significantly reduces the porosity of concrete, but also improves its impermeability and ability to resist freeze-thaw cycles, thereby improving overall durability.

[0206] Comparative experiment 2: Comparative experiment of plant ash treatment process

[0207] Experimental group: The treatment group of the present invention: using plant ashes treated with alkali and heat.

[0208] Comparative Example 3: Untreated ash group: plant ashes that were not subjected to alkali treatment and heat treatment were used.

[0209] The concrete formula for both groups is the same, as follows:

[0210] 100 parts of ordinary Portland cement, 25 parts of plant ash, 15 parts of silica fume, 8 parts of limestone powder, 105 parts of quartz sand, 19 parts of water, 1.0 part of polycarboxylic acid water reducing agent, and bamboo fiber (2.5% volume ratio).

[0211] The concrete experimental procedures for the two groups were the same as those for comparative experiment 1.

[0212] The experimental results are shown in the following table:

[0213] Test items Experimental group (handled ash) Comparative Example 3 (untreated ash) Compressive strength (MPa, 28 days) 135 115 Flexural strength (MPa, 28 days) 28 22 Slump(mm) 190 195 Porosity (%) 4.5 6 Impermeability (water penetration depth mm) 12 20 CSH gel content (XRD results, %) 38 30 <![CDATA[Residual content of Ca(OH)2 (XRD result, %)]]> 8.5 14

[0214] From the data in the above table, we can get:

[0215] 1. Comparison of mechanical properties:

[0216] The compressive strength of the experimental group (treated ash) reached 135MPa and the flexural strength was 28MPa at 28 days, while the compressive strength and flexural strength of the comparative example 3 (untreated ash) were 115MPa and 22MPa respectively. The treated plant ash can fully react with Ca(OH)2 in the cement matrix due to its activated SiO2 to generate more CSH gel, thus significantly improving the strength of the concrete.

[0217] The low pozzolanic activity of untreated ash results in less CSH gel production and limited mechanical properties.

[0218] 2. Comparison between fluidity and slump:

[0219] The difference in slump between the two groups was small, indicating that the plant ash treatment process had no significant adverse effect on the fluidity of concrete and maintained good construction performance.

[0220] 3. Comparison of porosity and impermeability:

[0221] The porosity of the experimental group was 4.5%, significantly lower than 6.0% of Comparative Example 3. The treated plant ash was able to generate more CSH gel, filling the pores of the concrete and reducing the water penetration path, making the water penetration depth only 12 mm, while the untreated ash group was 20 mm.

[0222] The CSH gel content of the experimental group reached 38%, while that of comparative example 3 was only 30%, which indicates that the treated plant ash can more effectively promote the secondary hydration reaction and enhance the density and impermeability of concrete.

[0223] 4. Comparison of residual calcium hydroxide content:

[0224] XRD results show that the residual content of Ca(OH)2 in the experimental group is only 8.5%, while the residual content in comparative example 3 is 14.0%. This indicates that the treated plant ash can more fully consume the Ca(OH)2 generated during cement hydration, and the efficiency of generating CSH gel is higher, which further improves the strength and durability of concrete.

[0225] The processing of plant ash greatly improves the volcanic ash activity. Alkali treatment can remove organic impurities in the ash and increase the reactivity of SiO2; heat treatment activates SiO2 in the ash, allowing it to fully react with calcium hydroxide (Ca(OH)2) in the cement matrix to generate more CSH gel. This reaction process not only significantly improves the compressive and flexural strength of concrete, but also enhances the density and impermeability of the material.

[0226] In contrast, although untreated plant ash still contains SiO2, its reactivity is lower, resulting in less CSH gel produced in the hydration reaction. It has higher porosity, more residual Ca(OH)2, longer water penetration path and poorer durability.

[0227] Comparative experiment 3: Comparative experiment between natural fiber (bamboo fiber) and traditional steel fiber

[0228] Experimental group: The present invention group (bamboo fiber): bamboo fiber treated with alkali and heat pressed was used.

[0229] Comparative Example 4: Conventional steel fiber group: Steel fibers of the same length were used.

[0230] The concrete formulas for the two groups are as follows:

[0231] Material Experimental group (bamboo fiber) Comparative Example 4 (Steel Fiber) Ordinary Portland Cement 100 copies 100 copies Plant Ashes 25 servings 25 servings Silica Fume 15 servings 15 servings Limestone powder 8 servings 8 servings Quartz sand 105 copies 105 copies water 19 servings 19 servings Polycarboxylate water reducer 1.0 copy 1.0 copy Bamboo Fiber 2.5% volume ratio (12mm length) - Steel Fiber - 2.5% volume ratio (12mm length)

[0232] Experimental steps:

[0233] 1. Fiber processing:

[0234] Experimental group: The bamboo fibers were treated with 4% NaOH solution at 65°C for 2.5 hours, and then dried and hot pressed at 90°C and 12 MPa for 45 minutes.

[0235] Comparative Example 4: Steel fibers were used directly without any additional treatment.

[0236] 2. Dry mixing:

[0237] Add cement, quartz sand, limestone powder, silica fume and plant ash into the mixer according to the proportion and stir at low speed for 2.5 minutes.

[0238] 3. Wet mixing:

[0239] The mixed solution of water and polycarboxylic acid water reducer was gradually added in 3 times, stirring for 4 minutes each time, and the plant ash was gradually added.

[0240] 4. Fiber addition and high-speed stirring:

[0241] Experimental group: bamboo fiber was added in 3 batches, stirred for 5 minutes each time, and finally stirred at high speed for 3 minutes.

[0242] Comparative Example 4: The steel fiber was added in 3 batches, each time stirred for 5 minutes, and finally stirred at high speed for 3 minutes.

[0243] 5. Molding and maintenance:

[0244] The concrete slurry is poured into the mold, subjected to vibration compaction treatment, and cured under standard conditions (20° C., 95% humidity) for 28 days after molding.

[0245] The experimental results are shown in the following table:

[0246]

[0247]

[0248] From the data in the above table, we can get:

[0249] 1. Comparison of mechanical properties:

[0250] Compressive strength: The steel fiber group performed slightly better in compressive strength, reaching 140MPa, while the bamboo fiber group was 135MPa. Steel fiber has a slight advantage in compressive strength due to its higher tensile strength.

[0251] Flexural strength: The flexural strength of the bamboo fiber group is 30MPa, slightly higher than the 28MPa of the steel fiber group. Bamboo fiber can more effectively inhibit crack expansion and improve the flexural performance of concrete due to its flexibility and dispersion.

[0252] 2. Comparison of toughness and crack resistance:

[0253] Impact toughness: The impact toughness of the bamboo fiber group is 45kJ / m 2 , much higher than the 30kJ / m of the steel fiber group 2 This is because bamboo fiber has good flexibility and can absorb more energy when impacted, delaying the expansion of cracks.

[0254] Crack extension: The crack width of the bamboo fiber group is 0.15mm, and the number is 3 / mm 2 , which is significantly better than the steel fiber group (crack width 0.25mm, number 6 / mm2 ). Bamboo fibers are evenly distributed in the concrete matrix and can effectively bridge cracks, reducing the width and number of cracks.

[0255] Crack resistance: The bamboo fiber group reached 6.5kN under cracking load, which was significantly higher than the 5.0kN of the steel fiber group, indicating that bamboo fiber has more outstanding crack resistance.

[0256] 3. Durability comparison:

[0257] After 100 freeze-thaw cycles, the mass loss rate of the bamboo fiber group was 2.0%, significantly lower than the 3.5% of the steel fiber group. Bamboo fiber can effectively reduce crack expansion and reduce material degradation caused by freeze-thaw cycles.

[0258] The flexibility and good dispersion of bamboo fiber enable it to form a uniform three-dimensional reinforcement network in the concrete matrix. Since bamboo fiber has a certain ductility and toughness, it can bridge cracks and delay crack expansion when concrete is tensile or impacted. This performance is particularly reflected in impact toughness and crack resistance. Bamboo fiber shows better crack control ability than steel fiber, reducing crack width and number, and extending the service life of concrete.

[0259] In contrast, although steel fibers have higher tensile strength, they are more rigid and tend to form wider cracks. In addition, the distribution of steel fibers in crack bridging is not as uniform as bamboo fibers, so they are slightly weaker in terms of crack resistance and toughness.

[0260] In terms of durability, bamboo fiber reduces the width and number of cracks, inhibits the entry of moisture and frozen materials into the concrete, and thus effectively improves the concrete's resistance to freeze-thaw cycles. Although steel fiber has a slightly higher compressive strength, due to the large number of cracks, the material deteriorates more significantly during freeze-thaw cycles.

[0261] Comparative experiment 4: Plant ash replacement rate comparison experiment

[0262] Experimental variables: Effects of different plant ash replacement rates (10%, 15%, 20%, 25%, 30%) on UHPC performance.

[0263] Comparative Examples 5-9: In the five comparative examples, different proportions (10%, 15%, 20%, 25%, and 30%) of plant ash were used to replace cement.

[0264] The concrete formulas of the five comparative examples are as follows:

[0265]

[0266]

[0267] Experimental procedures

[0268] 1. Plant ash treatment:

[0269] All groups: Plant ashes were alkaline treated with 3% NaOH solution at 60°C for 3 hours. The treated ashes were washed with distilled water until neutral, dried at 50-60°C for 12 hours, and then heat treated at 650°C for 1.5 hours.

[0270] 2. Bamboo fiber processing:

[0271] All groups: The bamboo fibers were treated with 4% NaOH solution at 65°C for 2.5 hours, and then dried and hot pressed at 90°C and 12 MPa for 45 minutes.

[0272] 3. Dry mixing:

[0273] Add cement, quartz sand, limestone powder, silica fume and plant ash into the mixer according to the proportion and stir at low speed for 2.5 minutes.

[0274] 4. Wet mixing:

[0275] The mixed solution of water and polycarboxylic acid water reducer was gradually added in 3 times, stirring for 4 minutes each time, and the plant ash was gradually added.

[0276] 5. Fiber addition and high-speed stirring:

[0277] Add the bamboo fiber in 3 batches, stirring for 5 minutes each time, and finally stirring at high speed for 3 minutes.

[0278] 6. Molding and maintenance:

[0279] The concrete slurry is poured into the mold, subjected to vibration compaction treatment, and cured under standard conditions (20° C., 95% humidity) for 28 days after molding.

[0280] The experimental results are shown in the following table:

[0281]

[0282] From the data in the above table, we can get:

[0283] 1. Comparison of mechanical properties:

[0284] Compressive strength: As the replacement rate of plant ash increases, the compressive strength gradually increases. At a replacement rate of 20-25%, the compressive strength reaches a peak value (140MPa), and when it exceeds 25%, the compressive strength decreases slightly (130MPa). This shows that when the replacement rate of plant ash is between 20-25%, the compressive strength of concrete can be best improved.

[0285] Flexural strength: As the substitution rate of plant ash increases, the flexural strength gradually increases. At 20-25% substitution rate, the flexural strength reaches 28-29MPa, and then decreases slightly, indicating that this substitution rate is the ideal range for optimizing flexural performance.

[0286] 2. Comparison between fluidity and slump:

[0287] As the replacement rate of plant ash increases, the fluidity of concrete gradually decreases. The slump gradually decreases from 195mm to 175mm, but it still remains within an acceptable range to meet construction requirements. Plant ash has a certain effect on the fluidity of concrete paste due to its high fineness and strong water absorption. Therefore, the higher the replacement rate, the lower the slump.

[0288] 3. Porosity and density:

[0289] The porosity decreases with the increase of plant ash replacement rate and reaches the minimum (4.3%) at 25% replacement rate, indicating that the density of concrete is significantly improved. This phenomenon can be explained by the reaction of active silica in plant ash with cement hydration products (Ca(OH)2) to form CSH gel.

[0290] CSH gel content: XRD analysis showed that the CSH gel content increased significantly with the increase of plant ash substitution rate, reaching a peak value (38-39%) at 20-25% substitution rate, further enhancing the density and mechanical properties of concrete.

[0291] 4. Durability comparison (freeze-thaw cycle loss rate):

[0292] After 100 freeze-thaw cycles, the experimental group with 20-25% plant ash replacement rate showed the lowest mass loss rate (2.0%), indicating good durability. When the replacement rate reached 30%, the freeze-thaw loss rate increased slightly, indicating that high replacement rate may have a certain negative impact on durability.

[0293] 5. Residual content of Ca(OH)2:

[0294] The pozzolanic activity of plant ash reacts with calcium hydroxide (Ca(OH)2) generated during cement hydration to form CSH gel. As the substitution rate increases, the residual content of Ca(OH)2 gradually decreases, and the Ca(OH)2 content is lowest when the substitution rate is 20-25%, indicating that the ash reacts most fully at this time and the ash replaces cement to achieve the best effect.

[0295] After alkali treatment and heat treatment, the active silica (SiO2) in plant ash can effectively react with cement hydration product Ca(OH)2 to generate a large amount of CSH gel. These CSH gels can fill the micropores in concrete, thereby significantly improving the density and mechanical properties of concrete. At a replacement rate of 20-25%, plant ash provides sufficient pozzolanic reaction substances to fully react with Ca(OH)2, reduce residual Ca(OH)2, and maximize the generation of CSH gel, so that both compressive strength and flexural strength reach peak values.

[0296] However, when the plant ash replacement rate exceeds 25%, the excessive addition of ash may lead to insufficient effective bonding in the cement matrix, thus causing the strength and durability of the concrete to begin to decline. In addition, the ash has strong water absorption, which causes the fluidity of the concrete paste to gradually decrease with the increase of the replacement rate, which also limits the upper limit of ash replacement.

[0297] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a new ultra-high performance concrete material using plant ash, characterized in that: The following steps are involved: The plant ashes are screened, crushed, chemically treated and thermally treated to obtain plant ashes with a particle size of 5-15 microns; Ordinary Portland cement, silica fume, fine aggregate, ultrafine powder and treated plant ash are dry-mixed and stirred; Gradually add water and superplasticizer mixed solution to the dry mix, and gradually add plant ash while stirring; Natural plant fibers are added to the wet mix and mixed at medium speed followed by high-speed mixing to obtain a uniform ultra-high performance concrete paste.

2. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The processing process of the plant ash includes: Sieving: Use a 200-mesh screen to sieve the plant ashes to remove particles larger than 75 microns; Crushing: The sieved plant ashes are crushed by crushing equipment to control the average particle size of the ashes to 5-15 microns.

3. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The chemical treatment of the plant ashes comprises the following steps: Use 2-5% sodium hydroxide solution to perform alkali treatment on plant ashes, the treatment temperature is controlled at 60-70°C, and the treatment time is 2-4 hours; The treated plant ashes were washed with distilled water until the pH of the solution was close to neutral; The cleaned plant ashes are dried in a constant temperature drying oven at 50-60°C for 12-24 hours.

4. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 3, characterized in that: The heat treatment temperature of the plant ash is 600-700° C., and the heat preservation time is 1-2 hours.

5. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 4, characterized in that: The silicon dioxide content of the treated plant ash is 60-75%.

6. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The processing of the natural plant fiber comprises the following steps: The fiber is alkali treated with a 3-5% sodium hydroxide solution at a temperature of 60-70°C for 2-3 hours; The alkali treated fiber is subjected to heat pressing treatment at a temperature of 80-100°C, a pressure of 10-15 MPa, and a time of 30-60 minutes.

7. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The proportions of cement, plant ash, silica fume, fine aggregate and ultrafine powder are as follows: Cement: silica fume: plant ash: limestone powder: quartz sand: water = 1: (0.15-0.25): (0.2-0.3): (0.05-0.1): (1-1.2): (0.18-0.22).

8. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The natural plant fiber is bamboo fiber, the fiber content is 2-3% of the total volume of the wet mixed material, and the fiber length is 8-15 mm.

9. The method for preparing a new ultra-high performance concrete material using plant ash according to claim 1, characterized in that: The superplasticizer is a polycarboxylic acid water reducer, the dosage of which is 0.8-1.2% of the mass of the cementitious material, and is wet mixed by gradually adding it 3-4 times.

10. Use of the ultra-high performance concrete prepared by the method according to any one of claims 1 to 9 in highway bridges, building structures and infrastructure.